A STUDY ON IMPACT OF EMPLOYEE WELFARE MEASURES INFLUENCING JOB SATISFACTION IN KSRTC IN BANGALORE - K N, Srinivasamurthy; K, Venkidasamy (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Employee welfare is in the interest of employee welfare, the employer and the society as a whole for the employee’s, welfare measures enable the employee’s and his family to lead good life welfare facilities like housing medical and children’s education, recreation etc. help to improve the family life to employee’s. Job satisfaction is a critical factor that influences the productivity and retention of employee’s in any organization. In the case of employee’s intensive sectors such as transportation, providing adequate welfare measures such as health, medical, and housing facilities becomes imperative to ensure workforce wellbeing. The Karnataka State Road Transport Corporation (KSRTC) has introduced various schemes to improve the living standards of its workers, but their impact on job satisfaction remains under explored. This research aims to a study on impact of employee welfare measures influencing job satisfaction in KSRTC in Bangalore. Descriptive research methodology was used in the present study. There were 623 employees have been surveyed in the KSRTC divisions across Bangalore on random basis. Structured survey questionnaire was used to collect the data. Regression analysis was used as statistical tool for the analysis purpose. It is found that, the unique contribution for the infrastructural welfare such as Counselling Centre, followed by Medical facility/Medical cheek up/Equipment, Seating facility, shelters, lunch room, First aid Boxes, Indoor and outdoor sports recreation facility, Preventive Medicine & Healthy life Style Clinic and Sufficient number of latrines and urinals, Rest Rooms, in predicting employees job satisfaction in KSRTC. The unique contribution for the general welfare such as Educational Assistance, followed by Free Family Bus Pass Card, Medical facilities for dependents/reimbursement, Traffic revenue incentive scheme, Transportation facilities, Housing facilities and Employee family welfare scheme, and Accident-free Drivers -Award schemes, in predicting employees job satisfaction in KSRTC.